Faktor Risiko Umur Lansia terhadap Kejadian Reaksi Obat yang Tidak Dikehendaki pada Pasien Hipertensi, Diabetes, Dislipidemia di Tiga Puskesmas di Kota Depok - Wulandari, Nora; Andrajati, Retnosari; Supardi, Sudibyo (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
Treatments in elderly patients are very complex and usually multiphatology thus causing an increase in number of polypharmacy for every clinical condition. The presence of hypertension, diabetes, and/or dyslipidemic will increase the risk of Adverse Drug Reaction (ADR) because of polypharmacy and long term of treatments. This study aimed to assess the effect of elderly age on the incidence of ADR in patients with hypertension, diabetes, and/or dyslipidemia at Puskesmas Pancoran Mas, Beji, and Tanah Baru in Depok. The design of the study is cohort study. The study was conducted at January-June 2014. Sixty two elderly patients were collected as cohort group and 62 non-elderly patients as control group. Subjects were monitored every week for a month. Clinical Manifestation of ADR event was an evaluation result of the recording complaints experienced by the subject using Naranjo scale. Clinical manifestation of ADR events obtained from both group were analyzed using Chi-square and Logistic Regression Test. This study found that 30,6% patients experienced ADR events with 39 times of accurrences. The most common clinical manifestation was dry cough related to the use of captopril (56,3%). The risk factor of ADR event in elderly age is 3,577 times greater than non-elderly age.